Improving phase retrieval accuracy of optical parallel plate by adjusting exposure time of CCD. (10th May 2021) - Liu, Xu; Liu, Yong; Li, Dong; He, Yuhang; Jiang, Hongzhen; Zhang, Huxiang; Ren, Huan; Chai, Liqun; Zhu, Qihua; Zheng, Wanguo; Tan, Qiaofeng
Abstract: A new phase retrieval method is investigated to reconstruct wavefronts of optical parallel plates with the use of a group of diffraction patterns. More specifically, the improved phase retrieval algorithm is realized by converting the measuring plane wave into a spherical wave and by using single or double discrete Fourier transforms to calculate both far- and near-field diffraction propagations, and the accuracy is improved by adjusting the exposure time of the charge-coupled device according to the distance between the focal plane and diffraction plane. Both the theoretical and experimental results are consistent with the results obtained using conventional wavelength-modulated phase-shifting interferometry. The new method opens new doors for realizing wavefront measurement of optical parallel plates with high accuracy, especially for large-aperture parallel plates in inertial confinement fusion laser systems.